Policing in the People's Republic of China: a review of recent literature - Dai, Mengyan (Crime, law and social change, 2008)
Recent literature on policing in the People's Republic of China, though very limited, has encompassed a wide range of topics including police organizations, roles and functions, subculture, policing strategies (such as community policing, campaign style policing, and the comprehensive management approach), and a number of issues and problems (such as abuse of power, accountability, and police citizen relations). These studies serve to establish a foundation for a better understanding of the complex social control in China. The present study summarizes the findings of recent research, identifies its limitations, and discusses the directions and challenges in future research.